Composite current collector, method for manufacturing the same, and negative electrode-free battery

CN122907642APending Publication Date: 2026-10-13JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610667600.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-14
Publication Date
2026-10-13

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of battery, in particular to a composite current collector, a preparation method thereof and a negative electrode-free battery. The composite current collector comprises: a current collector substrate; a first functional layer arranged on at least one side surface of the current collector substrate along the thickness direction, wherein the first functional layer comprises hollow mesoporous silica loaded with a functional material; and a second functional layer arranged on the surface of the first functional layer away from the current collector substrate, wherein the second functional layer comprises a dielectric material; wherein the functional material is loaded in the pore channel of the hollow mesoporous silica, and the functional material comprises a lithium salt; and the dielectric constant of the dielectric material is 1.2-3. The battery comprising the composite current collector has excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a composite current collector, its preparation method, and a negative electrode-free battery. Background Technology

[0002] In the field of lithium-ion battery technology, in order to overcome the theoretical capacity limitations of traditional graphite anode materials and improve the energy density of batteries, using metallic lithium as the anode active material has become an important research direction. Among them, anode-free lithium metal batteries, by placing the lithium source entirely on the positive electrode side and depositing lithium on the negative electrode current collector during charging, can significantly reduce the use of inactive materials, thereby theoretically achieving a higher energy density.

[0003] To achieve this goal, related technologies typically focus on using unmodified metal current collectors (such as copper foil) directly as the negative electrode substrate. However, due to the inherent physicochemical properties of the current collector surface, especially its poor affinity with metallic lithium, lithium ions tend to nucleate and grow unevenly during electrochemical deposition. This uneven deposition behavior easily leads to the rampant growth of lithium dendrites, irreversible loss of active lithium, and instability of the solid electrolyte interface film, ultimately severely impairing the cycle life and safety of the battery.

[0004] Therefore, in anode-free lithium metal battery systems, how to guide lithium ions to achieve uniform and reversible deposition and stripping on the surface of the anode current collector, thereby effectively suppressing harmful side reactions and improving cycle stability, has become a key technical problem that urgently needs to be solved. Summary of the Invention

[0005] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a composite current collector, a method for preparing the same, and a negative electrode-free battery. This composite current collector can guide lithium ions to achieve uniform and reversible deposition and stripping.

[0006] To solve the above-mentioned technical problems, this application is implemented as follows: According to one aspect of this application, an embodiment of this application provides a composite current collector, the composite current collector comprising: Current collector substrate; A first functional layer is disposed on at least one side surface of the current collector substrate along the thickness direction, and the first functional layer includes hollow mesoporous silica loaded with functional material. A second functional layer is disposed on the surface of the first functional layer away from the current collector substrate, and the second functional layer includes a dielectric material; The functional material is loaded within the hollow mesoporous silica channels, and the functional material includes lithium salt; The dielectric constant of the dielectric material is 1.2~3.

[0007] In some of these embodiments, the loading rate of the hollow mesoporous silica loaded with functional materials is 30% to 60%.

[0008] In some embodiments, the lithium salt includes at least one of lithium nitrate, lithium difluorophosphate, and lithium fluoroborate.

[0009] In some embodiments, the first functional layer further includes a first adhesive, which includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, and lithium carboxymethyl cellulose.

[0010] In some of these embodiments, the mass ratio of the hollow mesoporous silica loaded with functional material to the first binder is (1~9):1.

[0011] In some of these embodiments, the thickness of the first functional layer is 3 μm to 10 μm.

[0012] In some embodiments, the dielectric material includes a ferroelectric material, which includes at least one of barium titanate, lithium tantalate, bismuth titanate, and lead titanate.

[0013] In some embodiments, the second functional layer further includes a second adhesive, which includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, and lithium carboxymethyl cellulose.

[0014] In some embodiments, the mass ratio of the dielectric material to the second adhesive is (1~9):1.

[0015] In some of these embodiments, the thickness of the second functional layer is 3 μm to 10 μm.

[0016] In some embodiments, the current collector substrate comprises a copper foil with a thickness of 4 μm to 8 μm.

[0017] According to another aspect of this application, embodiments of this application provide a method for preparing a composite current collector, comprising the following steps: A first functional slurry is coated on at least one side surface of a current collector substrate, and a first functional layer is obtained after a first drying process. A second functional slurry is coated on the surface of the first functional layer, and after drying, a composite current collector is obtained. The first functional paste includes hollow mesoporous silica loaded with functional materials, and the second functional paste includes dielectric materials.

[0018] In some embodiments, the method for preparing the hollow mesoporous silica loaded with functional materials includes: Hollow mesoporous silica was mixed with a lithium salt solution, soaked, filtered, washed, and dried to obtain hollow mesoporous silica loaded with functional materials.

[0019] In some embodiments, the molar ratio of the hollow mesoporous silica to the lithium salt solution is (0.5~1):1.

[0020] In some embodiments, the lithium salt solution is an aqueous solution of lithium salt, and the concentration of the lithium salt solution is 0.3 mol / L to 1 mol / L.

[0021] In some of these embodiments, the soaking time is 8 to 16 hours.

[0022] In some embodiments, the preparation of the first functional slurry includes: Hollow mesoporous silica loaded with functional materials and a first binder are mixed in a first solvent to obtain a first functional slurry.

[0023] In some of these embodiments, the first solvent includes N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl carbonate.

[0024] In some of these embodiments, the solid content of the first functional slurry is 30% to 50%.

[0025] In some embodiments, the preparation of the second functional slurry includes: The dielectric material and the second binder are mixed in the second solvent to obtain the second functional slurry.

[0026] In some embodiments, the second solvent includes N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl carbonate.

[0027] In some of these embodiments, the solid content of the second functional slurry is 30% to 50%.

[0028] According to another aspect of this application, an embodiment of this application provides a negative electrode-free battery, including a negative electrode current collector, wherein the negative electrode current collector includes the aforementioned composite current collector, or includes a composite current collector prepared according to the aforementioned preparation method.

[0029] Implementing the technical solution of the present invention has at least the following beneficial effects: In this embodiment, by setting a first functional layer comprising hollow mesoporous silica loaded with functional materials, this layer can continuously release beneficial components such as lithium salts in situ during battery cycling, thereby optimizing and stabilizing the SEI film composition on the negative electrode surface, effectively reducing the nucleation overpotential of lithium deposition, and reducing the irreversible consumption of active lithium in side reactions. Simultaneously, by setting a second functional layer containing high-dielectric materials, this layer can promote the dissociation of lithium salts, generate a uniform electric field during polarization, suppress the formation of a space charge layer, regulate lithium-ion transport, uniformly distribute the lithium flux at the interface, achieve uniform lithium deposition and stripping, reduce the formation of inactive lithium, and improve the significant loss of reversible capacity during cycling. This application, by setting the first and second functional layers, works synergistically to reduce lithium dendrite formation, dead lithium phenomena, and achieve high-rate performance, thereby improving the coulombic efficiency and cycle performance of anode-less lithium metal batteries.

[0030] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation

[0031] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0032] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0033] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0034] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0035] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0036] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0037] In the field of negative electrode-less lithium batteries, to suppress lithium dendrite growth and improve cycle life, surface modification of the negative electrode current collector is commonly employed. Specifically, this is achieved by constructing an artificial solid electrolyte interface film or a three-dimensional conductive framework. The basic working principle involves coating or constructing a functional coating on the surface of current collectors such as copper foil to guide lithium-ion deposition by physically blocking or providing more nucleation sites. Its widespread application is primarily due to its ability to improve the uniformity of initial lithium deposition and slow down dendrite penetration.

[0038] However, when this approach is applied to electrodeless batteries with stringent requirements for long cycle life, its performance is less than ideal. The fundamental contradiction lies in the fact that the static or single-functional coatings designed to improve initial deposition uniformity continuously degrade or fail during long-term cycling, making it difficult to dynamically maintain interface stability. They may even exacerbate side reactions due to component consumption or structural damage. Specifically, during repeated charge-discharge cycles, the functional additives in the coating are irreversibly and rapidly consumed, leading to a decrease in the solid electrolyte interface film repair capability in subsequent cycles. Simultaneously, the lithium-ion concentration field and electric field distribution at the current collector-electrolyte interface are difficult to effectively control, and the space charge effect causes subsequent lithium deposition to become non-uniform again, ultimately leading to dendrite growth and loss of active lithium.

[0039] In view of this, embodiments of this application provide a composite current collector, the composite current collector comprising: Current collector substrate; A first functional layer is disposed on at least one side surface of the current collector substrate along the thickness direction, and the first functional layer includes hollow mesoporous silica loaded with functional material. A second functional layer is disposed on the surface of the first functional layer away from the current collector substrate, and the second functional layer includes a dielectric material; The functional material is loaded within the hollow mesoporous silica channels, and the functional material includes lithium salt; The dielectric constant of the dielectric material is 1.2~3.

[0040] In this application, the provided composite current collector has a multilayer structure, which includes a current collector substrate, a first functional layer, and a second functional layer stacked in sequence. That is, the first functional layer is disposed on at least one side surface of the current collector substrate, and the second functional layer is disposed on the surface of the first functional layer.

[0041] The phrase "the first functional layer is disposed on at least one surface of the current collector substrate along its thickness direction" means that the first functional layer can be disposed on one surface of the current collector substrate along its own thickness direction, or it can be disposed on two surfaces of the current collector substrate along its own thickness direction. Here, "surface" can be the entire area of ​​the current collector substrate or a part of the current collector substrate. As in this embodiment, the surface can be the entire area of ​​the current collector substrate. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.

[0042] As an example, the current collector substrate has two surfaces opposite each other in its thickness direction, and a first functional layer is disposed on the two opposite surfaces of the current collector substrate. Furthermore, a second functional layer is formed on each surface of the first functional layer on both sides. It is understood that in other embodiments, the first functional layer may also be stacked on either of the two surfaces of the current collector substrate.

[0043] In this application, "dielectric material" refers to any material with a high dielectric constant that can be polarized under the influence of an electric field, thereby affecting the distribution of the interfacial electric field. A dielectric constant in the range of 1.2 to 3 is suitable for this application to effectively adjust the interfacial electric field.

[0044] In this application, the dielectric constant can be tested using the parallel plate capacitor method. Specifically, the dried powder is cold-pressed into a sheet with a diameter of 10 mm, and calculations are performed at 1,000,000 Hz. Based on the obtained real and imaginary impedances, the capacitance value C is calculated according to Formula 1, and then the dielectric constant is calculated according to Formula 2. Formula (1) is: C = Z" / 2πf(Z') 2 +Z" 2 ) ; Where C: measured capacitance (unit: Farad, F); Z': real part of impedance; Z": imaginary part of impedance; f: Frequency (Hz, here it is 1,000,000); Formula (2) is: εr=C d / (A ε0); Where: C: measured capacitance (unit: Farad, F); d: cold-pressed sheet thickness (unit: Meter, m); ε0: vacuum dielectric constant (8.854 × 10⁻⁶). -12 F / m, a fixed value); A: Effective electrode area (unit: m²) 2 In this application, the material of the current collector substrate for the composite current collector is not specifically limited. For example, it can be copper foil.

[0045] Based on the above, this application optimizes and stabilizes the SEI film composition on the negative electrode surface by setting a first functional layer comprising hollow mesoporous silica loaded with functional materials. This first functional layer enables the continuous in-situ release of beneficial components such as lithium salts during battery cycling, thereby effectively reducing the nucleation overpotential of lithium deposition and minimizing the irreversible consumption of active lithium in side reactions. Simultaneously, by setting a second functional layer containing high-dielectric materials, this layer promotes the dissociation of lithium salts, generates a uniform electric field during polarization, suppresses the formation of a space charge layer, regulates lithium-ion transport, and uniformizes the interfacial lithium flux, achieving uniform lithium deposition and stripping, reducing the formation of inactive lithium, and mitigating significant capacity loss during cycling. Through the synergistic effect of the first and second functional layers, this application reduces lithium dendrite formation and dead lithium phenomena, achieves high-rate performance, and improves the coulombic efficiency and cycle performance of negative electrode-less lithium metal batteries.

[0046] In some specific embodiments, the loading rate of the hollow mesoporous silica loaded with functional materials is 30% to 60%, for example, it can be 30%, 45%, 60%, or other values ​​within the above range. Controlling the loading rate within the range of 30% to 60% ensures sufficient functional material reserves within the pores to support long-term sustained-release requirements and maintain the continuous stability of the SEI. This avoids the problems of insufficient effective components and short-lived effects caused by excessively low loading rates, and also avoids the risks of pore blockage, deteriorated lithium salt release kinetics, or even carrier structure rupture that may occur with excessively high loading rates. Thus, a controlled and durable interfacial chemical modification effect is achieved.

[0047] In some specific embodiments, the lithium salt includes at least one of lithium nitrate, lithium difluorophosphate, and lithium fluoroborate. For example, it can be lithium nitrate or lithium difluorophosphate.

[0048] In some specific embodiments, the first functional layer further includes a first adhesive, which includes at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, and lithium carboxymethyl cellulose. For example, it can be polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene.

[0049] In some specific embodiments, the mass ratio of the hollow mesoporous silica loaded with functional materials to the first binder is (1~9):1, for example, it can be 1:1, 5:1, 9:1, or other ratios within the above range, preferably 1:1. Sufficient first binder (such as PVDF) ensures a strong bond between functional particles and between the coating and the current collector substrate, ensuring the structural integrity of the coating during cycling. Furthermore, a larger amount of first binder enhances the toughness of the first functional layer, preventing rapid breakage of the hollow mesoporous silica during battery cycling. Simultaneously, limiting the binder ratio prevents over-encapsulation of functional particles, which could hinder their contact with the electrolyte, ensuring effective release of the functional materials or effective polarization of the dielectric materials. This balance allows the functional layer to withstand the mechanical stress of the electrochemical process while efficiently performing its intended electrochemical function.

[0050] In some specific embodiments, the thickness of the first functional layer is 3 μm to 10 μm, for example, it can be 3 μm, 5 μm, 8 μm, 10 μm, or other values ​​within the above range. On the one hand, this thickness is sufficient to accommodate the necessary amount of functional material, ensuring that its functional reserves can meet long-term cycling requirements; on the other hand, it is thin enough not to significantly increase ion transport distance and interfacial impedance, thereby avoiding negative impacts on battery rate performance and energy density. Furthermore, an appropriate thickness helps the coating maintain good mechanical integrity and adhesion during volume changes caused by lithium deposition / stripping, preventing cracking or peeling.

[0051] In some specific embodiments, the dielectric material includes a ferroelectric material, which includes at least one of barium titanate, lithium tantalate, bismuth titanate, and lead titanate. For example, it can be barium titanate or lithium tantalate.

[0052] In some specific embodiments, the second functional layer further includes a second adhesive, which includes at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, and lithium carboxymethyl cellulose. For example, it can be polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene.

[0053] In some specific embodiments, the mass ratio of the dielectric material to the second adhesive is (1~9):1, for example, it can be 1:1, 5:1, 9:1, etc., or other ratios within the above range, preferably 1:1. Where the mass ratio of the dielectric material to the second adhesive is within the above range, it can ensure that the coating remains in close contact with the copper foil during repeated lithium deposition and peeling processes, preventing the modification layer from powdering and peeling off.

[0054] In some specific embodiments, the thickness of the second functional layer is 3μm to 10μm, for example, it can be 3μm, 5μm, 8μm, 10μm, or other values ​​within the above range. This thickness range ensures that the dielectric layer has sufficient volume to accommodate a sufficient amount of high-dielectric material, thereby generating a sufficiently strong and uniform polarization electric field during battery operation. This effectively regulates the lithium-ion concentration field at the interface and guides uniform lithium-ion transport. Simultaneously, the thickness is strictly controlled within the above range to avoid the problems of excessively long lithium-ion cross-film transport paths and significantly increased interface impedance caused by an excessively thick dielectric layer, thus preventing negative impacts on battery rate performance and energy density. Furthermore, the suitable thickness also ensures that this layer maintains good mechanical synergy and structural integrity with the adjacent first functional layer during long-term charge-discharge cycles, jointly withstanding the volume change stress during lithium deposition / stripping, maintaining the stability of the overall functional coating, and ultimately achieving a more efficient and durable dendrite suppression effect.

[0055] In some specific embodiments, the current collector substrate includes a copper foil with a thickness of 4μm to 8μm, for example, 4μm, 6μm, 8μm, or other values ​​within the above range.

[0056] Based on the same inventive concept, this application provides a method for preparing a composite current collector, comprising the following steps: A first functional slurry is coated on at least one side surface of a current collector substrate, and a first functional layer is obtained after a first drying process. A second functional slurry is coated on the surface of the first functional layer, and after drying, a composite current collector is obtained. The first functional paste includes hollow mesoporous silica loaded with functional materials, and the second functional paste includes dielectric materials.

[0057] It should be understood that all the features and advantages described above regarding the "composite current collector" also apply to the "preparation method of the composite current collector," and will not be repeated here.

[0058] In some specific embodiments, the method for preparing the hollow mesoporous silica loaded with functional materials includes: Hollow mesoporous silica was mixed with a lithium salt solution, soaked, filtered, washed, and dried to obtain hollow mesoporous silica loaded with functional materials.

[0059] In some specific embodiments, the molar ratio of the hollow mesoporous silica to the lithium salt solution is (0.5~1):1, for example, it can be 0.5:1, 0.8:1, 1:1, or other ratios within the above range.

[0060] In some specific embodiments, the lithium salt solution is an aqueous lithium salt solution, and the concentration of the lithium salt solution is 0.3 mol / L to 1 mol / L, for example, it can be 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, or other values ​​within the above range.

[0061] In some specific embodiments, the soaking time is 8h to 16h, for example, it can be 8h, 12h, 16h, or other values ​​within the above range.

[0062] In this application, by controlling parameters such as the molar ratio of hollow mesoporous silica to lithium salt solution, the concentration of lithium salt solution, and soaking time, the loading of lithium salt in the porous carrier channels can be precisely controlled, so that it stably falls within the optimal filling rate range of 30%-60%.

[0063] In some specific embodiments, the preparation of the first functional slurry includes: Hollow mesoporous silica loaded with functional materials and a first binder are mixed in a first solvent to obtain a first functional slurry.

[0064] In some specific embodiments, the first solvent includes N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl carbonate. For example, it can be N-methylpyrrolidone or N,N-dimethylformamide.

[0065] In some specific embodiments, the solid content of the first functional slurry is 30% to 50%, for example, it can be 30%, 40%, 50%, etc., or it can be other values ​​within the above range.

[0066] In some specific embodiments, the preparation of the second functional slurry includes: The dielectric material and the second binder are mixed in the second solvent to obtain the second functional slurry.

[0067] In some specific embodiments, the second solvent includes N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl carbonate. For example, it can be N-methylpyrrolidone or N,N-dimethylformamide.

[0068] In some specific embodiments, the solid content of the second functional slurry is 30% to 50%, for example, it can be 30%, 40%, 50%, etc., or it can be other values ​​within the above range.

[0069] Based on the same inventive concept, embodiments of this application provide a negative electrode-free battery, including a negative electrode current collector, wherein the negative electrode current collector includes the aforementioned composite current collector, or includes a composite current collector prepared according to the aforementioned preparation method.

[0070] Because this battery contains the composite current collector provided in the embodiments of this application, it has superior cycle performance.

[0071] In some embodiments, the battery can be a lithium-ion battery. The battery stacking type is, for example, a wound or stacked battery, and the structural type is, for example, a prismatic (aluminum, steel, etc.) battery, a pouch battery, or a cylindrical battery, etc., without specific limitations. This battery has excellent cycle performance.

[0072] In some embodiments, the battery further includes a positive electrode, an electrolyte, and a separator. That is, the battery includes a positive electrode, a composite current collector, an electrolyte, and a separator.

[0073] In this embodiment, the materials and structures of the positive electrode current collector, the conductive agent and the binder in the positive electrode active material layer are not limited, and the positive electrode structure and composition known in the art that can be used in secondary batteries can be selected.

[0074] In this embodiment, the specific material or type of the separator is not limited, and any separator known in the art that can be used in secondary batteries can be selected.

[0075] It should also be noted that the battery in this application does not limit the specific material or type of electrolyte. Any components and types known in the art that can be used in secondary batteries can be selected, as long as the purpose of this application can be achieved.

[0076] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.

[0077] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0078] Example 1 Prepare 200 mL of 0.5 M / L lithium nitrate aqueous solution, add 10 g of dried hollow mesoporous silica to the above solution, stir at room temperature for 12 h, and let stand under vacuum at room temperature for 1 h to ensure full penetration of lithium nitrate. After centrifugation and washing, dry under vacuum at 80 °C to obtain hollow mesoporous silica loaded with lithium nitrate (loading rate 50%).

[0079] Hollow mesoporous silica loaded with lithium nitrate and polyvinylidene fluoride (PVDF) were dissolved in N-methylpyrrolidone (NMP) solution at a mass ratio of 1:1. The mixture was ultrasonicated and stirred to obtain a uniformly dispersed slurry. This slurry was then coated onto the surface of an 8 μm thick copper foil using a doctor blade to obtain the first functional layer (5 μm thick). Lithium titanate and PVDF were dissolved in NMP solution at a mass ratio of 1:1. The mixture was ultrasonicated and stirred to obtain a uniformly dispersed slurry. This slurry was then coated onto the surface of the first functional layer using a doctor blade to obtain the second functional layer (5 μm thick). The final composite current collector was thus obtained.

[0080] Example 2 The difference between Example 2 and Example 1 is that the thickness of the first functional layer and the second functional layer in Example 2 is 10 μm.

[0081] Example 3 The difference between Example 3 and Example 1 is that, in Example 3, when preparing the first functional layer, hollow mesoporous silica loaded with lithium nitrate and polyvinylidene fluoride (PVDF) were prepared in a mass ratio of 9:1. When preparing the second functional layer, lithium titanate and polyvinylidene fluoride (PVDF) are mixed at a mass ratio of 9:1.

[0082] Example 4 The difference between Example 4 and Example 1 is that the thickness of the first functional layer and the second functional layer in Example 4 is 3 μm.

[0083] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the mixture was stirred at room temperature for 10 hours and then allowed to stand under vacuum at room temperature for 0.5 hours to obtain hollow mesoporous silica loaded with lithium nitrate (loading rate of 30%).

[0084] Example 6 The difference between Example 6 and Example 1 is that Example 6 was stirred at room temperature for 12 hours and then allowed to stand under vacuum at room temperature for 2 hours to obtain hollow mesoporous silica loaded with lithium nitrate (loading rate of 60%).

[0085] Example 7 The difference between Example 7 and Example 1 is that in Example 7, lithium nitrate is replaced with lithium difluorophosphate.

[0086] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not include a second functional layer.

[0087] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not include a first functional layer.

[0088] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 does not include a first functional layer and a second functional layer.

[0089] Performance testing 1. Battery manufacturing Preparation of the positive electrode: NCM623, PVDF, and conductive carbon were mixed in a mass ratio of 90:5:5. Then, N-methylpyrrolidone (NMP) was added, and the mixture was stirred and homogenized to form a stable positive electrode slurry. The positive electrode slurry was coated onto aluminum foil (13 μm thick) using a 200 μm scraper. After drying, it was cut into small round pieces with a diameter of 14 mm for later use. The active material mass of the electrode was controlled at 2.2 mg / cm³. 2 .

[0090] Separator: A polyethylene (PE) membrane with a thickness of 9μm is selected as the separator.

[0091] Electrolyte: In a glove box filled with inert gas, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate are mixed in a mass ratio of 1:1:1 to obtain an organic solvent. Fluorinated ethylene carbonate is then added at 10% of the total volume of the organic solvent. Lithium salt LiPF6 is then dissolved in the organic solvent at a concentration of 1 mol / L to obtain the electrolyte.

[0092] Assemble a button cell using the above-mentioned positive electrode, separator, electrolyte, and composite current collector prepared in the embodiments or comparative examples of this application, with 100 μl of electrolyte added to each cell.

[0093] 2. Perform electrochemical performance testing on the battery. Capacity retention rate testing: The test temperature was 25℃, and the test voltage range was 2.8-4.3V. The batteries prepared in each embodiment and comparative example were connected to a charging cabinet. First, they were charged and discharged at 0.1C for two cycles to activate the batteries. Then, they were charged and discharged at 0.5C / 1C (0.5C charging to 4.3V, resting for 10 minutes; 1C discharging to 2.8V, resting for 10 minutes). The capacity of the first cycle was recorded as C0. The ratio of the discharge capacity of each subsequent cycle to C0 is the capacity retention rate; 1C = 0.609mA, and the resting time between charge and discharge was set to 10 minutes. The number of cycles for each embodiment and comparative example was recorded when the capacity retention rate was 70%.

[0094] Coulombic efficiency test: Batteries prepared in each example and comparative example were tested for coulombic efficiency under the following conditions: charge / discharge current of 1 A / g, charging cutoff voltage of 4.3 V, and discharging cutoff voltage of 2.5 V. The number of test cycles for each example and comparative example corresponded to the number of cycle cycles for their respective capacity retention tests (e.g., the number of cycle cycles for Example 1 was 194). The coulombic efficiency for each cycle was recorded. The average coulombic efficiency for all cycle counts was recorded as the average coulombic efficiency.

[0095] The test results are shown in Table 1.

[0096] Table 1 Under the same cutoff conditions, a higher number of cycles indicates better cycle performance, meaning less irreversible capacity loss in each cycle, higher reversibility of active lithium ion deposition and stripping, and less loss of active lithium due to internal side reactions and dendrite consumption. Table 1 shows that Examples 1-7 have higher cycle lives than Comparative Examples 1-3, indicating that the presence of the first and second functional layers can form a stable SEI, regulate lithium ion transport, and uniformly distribute interfacial lithium flux, ultimately achieving a higher cycle life.

[0097] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0098] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0099] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0100] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite current collector, characterized in that, The composite current collector includes: Current collector substrate; A first functional layer is disposed on at least one side surface of the current collector substrate along the thickness direction, and the first functional layer includes hollow mesoporous silica loaded with functional material. A second functional layer is disposed on the surface of the first functional layer away from the current collector substrate, and the second functional layer includes a dielectric material; The functional material is loaded within the hollow mesoporous silica channels, and the functional material includes lithium salt; The dielectric constant of the dielectric material is 1.2~3.

2. The composite current collector according to claim 1, characterized in that, The loading rate of the hollow mesoporous silica loaded with functional materials is 30%~60%; and / or, The lithium salt includes at least one of lithium nitrate, lithium difluorophosphate, and lithium fluoroborate.

3. The composite current collector according to claim 1, characterized in that, The first functional layer satisfies at least one of the following features (1) to (2): (1) The first functional layer further includes a first adhesive, which includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, and lithium carboxymethyl cellulose; Preferably, the mass ratio of the hollow mesoporous silica loaded with functional material to the first binder is (1~9):1; (2) The thickness of the first functional layer is 3μm~10μm.

4. The composite current collector according to claim 1, characterized in that, The second functional layer satisfies at least one of the following features (1) to (3): (1) The dielectric material includes ferroelectric materials, and the ferroelectric materials include at least one of barium titanate, lithium tantalate, bismuth titanate, and lead titanate; (2) The second functional layer further includes a second adhesive, which includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, and lithium carboxymethyl cellulose; Preferably, the mass ratio of the dielectric material to the second adhesive is (1~9):1; (3) The thickness of the second functional layer is 3μm~10μm.

5. The composite current collector according to claim 1, characterized in that, The current collector substrate includes copper foil with a thickness of 4μm to 8μm.

6. The method for preparing the composite current collector according to any one of claims 1 to 5, characterized in that, Includes the following steps: A first functional slurry is coated on at least one side surface of a current collector substrate, and a first functional layer is obtained after a first drying process. A second functional slurry is coated on the surface of the first functional layer, and after drying, a composite current collector is obtained. The first functional paste includes hollow mesoporous silica loaded with functional materials, and the second functional paste includes dielectric materials.

7. The method for preparing the composite current collector according to claim 6, characterized in that, The method for preparing the hollow mesoporous silica loaded with functional materials includes: Hollow mesoporous silica was mixed with a lithium salt solution, soaked, filtered, washed, and dried to obtain hollow mesoporous silica loaded with functional materials. The molar ratio of the hollow mesoporous silica to the lithium salt solution is (0.5~1):1; The lithium salt solution is an aqueous solution of lithium salt, and the concentration of the lithium salt solution is 0.3 mol / L to 1 mol / L; The soaking time is 8h to 16h.

8. The method for preparing the composite current collector according to claim 6, characterized in that, The preparation of the first functional slurry includes: Hollow mesoporous silica loaded with functional materials and a first binder are mixed in a first solvent to obtain a first functional slurry. The first solvent includes N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl carbonate; The solid content of the first functional slurry is 30%~50%.

9. The method for preparing the composite current collector according to claim 6, characterized in that, The preparation of the second functional slurry includes: The dielectric material and the second binder are mixed in the second solvent to obtain the second functional slurry. The second solvent includes N-methylpyrrolidone, N,N-dimethylformamide, and dimethyl carbonate; The solid content of the second functional slurry is 30%~50%.

10. A negative electrode-free battery, comprising a negative electrode current collector, characterized in that, The negative electrode current collector includes the composite current collector according to any one of claims 1 to 5, or the composite current collector prepared by the preparation method according to any one of claims 6 to 9.